Experimental and numerical investigations of the flexural behaviour ‎of Green - Ultra High Performance Fiber Reinforced Concrete ‎beams under repeated loads (Fracture and Structural Integrity, 2023)
There are various benefits to ultra-high-performance fiber-reinforced concrete ‎‎(UHPFRC). However, using a lot of cement in this type of concrete has a severe disadvantage since it causes pollution and several environmental concerns. Therefore, another type of concrete that achieves the same superior properties as UHPFRC while using less cement in the mixture should be considered. This research examined replacing cement with fly ash to produce environmentally friendly concrete called Green-UHPFRC. The impact of utilizing G-UHPFRC on the flexural behaviour of thirteen beams was investigated experimentally and numerically under repeated loads. The major parameters of the study were fly ash replacement ratios of 15%, 30%, and 45% and adding steel fiber to mixes with ratios of 1, 2, 3, and 4%. The tested beams were compared to the control beam in their backbone and hysteresis curves, failure load, crack propagation and failure modes, energy dissipation, stiffness degradation, and ductility index. From the results obtained, environmentally friendly concrete (G-UHPFRC) can be produced by replacing cement with fly ash up to 45% and adding 2% steel fiber without affecting the bending performance of beams made of G-UHPFRC compared to those made of UHPFRC.
Keywords: Fly ash; flexural behaviour; Cyclic loading; beams; Steel fiber; ansys